Analysis of mutant and total huntingtin expression in Huntington’s disease murine models - Valentina Fodale (Nature Portfolio, 2020)
Abstract Huntington’s disease (HD) is a monogenetic neurodegenerative disorder that is caused by the expansion of a polyglutamine region within the huntingtin (HTT) protein, but there is still an incomplete understanding of the molecular mechanisms that drive pathology. Expression of the mutant form of HTT is a key aspect of diseased tissues, and the most promising therapeutic approaches aim to lower expanded HTT levels. Consequently, the investigation of HTT expression in time and in multiple tissues, with assays that accurately quantify expanded and non-expanded HTT, are required to delineate HTT homeostasis and to best design and interpret pharmacodynamic readouts for HTT lowering therapeutics. Here we evaluate mutant polyglutamine-expanded (mHTT) and polyglutamine-independent HTT specific immunoassays for validation in human HD and control fibroblasts and use to elucidate the CSF/brain and peripheral tissue expression of HTT in preclinical HD models.